HOW THE CAPITAL MARKET REACTS BEFORE AND AFTER THE 2024 INDONESIAN PRESIDENTIAL ELECTION - Yoshua Fanuel Kobar; Agustina Ratna Dwiati; Riski Aprillia Nita (Reviu Accounting, Business & Organizations, 2025)
Research Objective - Analyzing capital market reactions ahead of and after the 2024 Indonesian presidential election. Method - The market reaction is examined through abnormal returns and trading volume activity, employing the paired sample t-test and the Wilcoxon signed-rank test as methods of statistical analysis. Findings - The Indonesian capital market did not provide a significant response to the 2024 Presidential Election event, either in the form of changes in abnormal returns or trading volume activity. At the announcement of the election results, the Indonesian capital market gave a reaction reflected in stock trading volume activity but there was no reaction in the form of abnormal returns. Theoretical and Policy Implications - Provides a more in-depth explanation of how political events, such as elections, can affect the capital markets. Research Novelty - Using the 2024 Election event study.